Phosphorylation Regulates the p31(Comet)-Mitotic Arrest-deficient 2 (Mad2) Interaction to Promote Spindle Assembly Checkpoint (SAC) Activity - Date, Dipali A. (American Society for Biochemistry and Molecular Biology, 2014)
The spindle assembly checkpoint (SAC) ensures the faithful segregation of the genome during mitosis by ensuring that sister chromosomes form bipolar attachments with microtubules of the mitotic spindle. p31(Comet) is an antagonist of the SAC effector Mad2 and promotes silencing of the SAC and mitotic progression. However, p31(Comet) interacts with Mad2 throughout the cell cycle. We show that p31(Comet) binds Mad2 solely in an inhibitory manner. We demonstrate that attenuating the affinity of p31(Comet) for Mad2 by phosphorylation promotes SAC activity in mitosis. Specifically, phosphorylation of Ser-102 weakens p31(Comet)-Mad2 binding and enhances p31(Comet)-mediated bypass of the SAC. Our results provide the first evidence for regulation of p31(Comet) and demonstrate a previously unknown event controlling SAC activity.